TNI AL Authority as Maritime Crime Investigator in Securing Indonesian Waters - Triadi, Irwan; Ardian, Muhammad Fadhil (Rechtsvinding, 2024)
This article aims to determine the authority of the Indonesian Navy as investigators of criminal offenses at sea, in line with their role in law enforcement in Indonesian waters. It examines the constraints faced by the Navy in law enforcement efforts and explores government measures to streamline these duties. The research method is normative legal research, which includes collecting, processing, and analyzing legal materials. The descriptive nature of this study connects factors with statutory regulations, theories, and expert opinions. A normative juridical approach is utilized, focusing on literature examination. The research concludes that the Indonesian Navy's authority as investigators in securing Indonesian waters is attributive, inherent to their office. From a constitutional law perspective, this attribution reflects the power of government organs to operate based on authority established by lawmakers, grounded in the constitution or legislation. According to the Law of the Republic of Indonesia Number 34 Year 2004 on the Indonesian National Armed Forces, Article 9, the Navy's role as law enforcement and security officers in Indonesian waters is hampered by unclear regulations. The Navy lacks authority to investigate all legal violations at sea, leading to overlapping law enforcement due to conflicting regulations that grant attributive authority.